1997
DOI: 10.1161/01.res.81.4.526
|View full text |Cite
|
Sign up to set email alerts
|

Alternatively Spliced IS6 Segments of the α 1C Gene Determine the Tissue-Specific Dihydropyridine Sensitivity of Cardiac and Vascular Smooth Muscle L-Type Ca 2+ Channels

Abstract: Dihydropyridines (DHPs) block the vascular smooth muscle L-type Ca2+ channel at lower concentrations than the cardiac Ca2+ channel, although their alpha 1 subunit, which binds the DHPs, is derived from the same gene. This alpha 1C gene gives rise to several splice variants, among which the alpha 1C-b variant is affected by lower concentrations of nisoldipine than the alpha 1C-a variant. Functional expression of chimeras of alpha 1C-a and alpha 1C-b subunits demonstrated that the transmembrane segment IS6 is re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
167
0
1

Year Published

1998
1998
2017
2017

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 202 publications
(178 citation statements)
references
References 24 publications
10
167
0
1
Order By: Relevance
“…Twenty to 30 bacterial colonies (derived from a single neuron) were then PCR amplified with splice-specific primers (bottom right, 220 bp), enabling determination of the ratio of EFa to EFb transcripts in individual neurons (Fig. 4 E) (Welling et al, 1997;Regan et al, 2000;Splawski et al, 2004;Fan et al, 2005). Whereas EFa and EFb were equivalent at 5 d, EFa predominated by 12 d. Although the relative increase of EFa transcript was less pronounced than the age-dependent elevation of CDF (Fig.…”
Section: Developmental Onset Of Neuronal Camentioning
confidence: 99%
“…Twenty to 30 bacterial colonies (derived from a single neuron) were then PCR amplified with splice-specific primers (bottom right, 220 bp), enabling determination of the ratio of EFa to EFb transcripts in individual neurons (Fig. 4 E) (Welling et al, 1997;Regan et al, 2000;Splawski et al, 2004;Fan et al, 2005). Whereas EFa and EFb were equivalent at 5 d, EFa predominated by 12 d. Although the relative increase of EFa transcript was less pronounced than the age-dependent elevation of CDF (Fig.…”
Section: Developmental Onset Of Neuronal Camentioning
confidence: 99%
“…Second generation blockers such as nimodipine display greater selectivity for vascular beds (11). Two mechanisms that contribute to this selectivity are: 1) state dependent block, where drugs preferentially block partially inactivated channels, and 2) tissue specific expression of Cav1.2 splice variants that have distinct sensitivity to the drugs (12).…”
Section: +mentioning
confidence: 99%
“…Welling et al (1997) showed that spliced variants of the IS6 segment of the a IC gene (a IC-a and a IC-b ) were speci®cally located in rat ventricular myocytes (a IC-a ) and in rat aorta (a IC-b ) and that nisoldipine showed greater sensitivity against the a IC-b vascular L-type channel than against the a IC-a cardiac channel. Thus the basis for vascular to cardiac selectivity of VOCC antagonists may involve the density and location of the broad type of VOCC (T and L), the possibility of alternative spliced segments of the critical voltage-gated pore protein, if located to speci®c tissues, and the resting membrane potential.…”
Section: Human Vascular To Cardiac Selectivitymentioning
confidence: 99%